A preliminary investigation on structural behaviour of concrete sleepers / Siti Hawa Hawizah, Bahardin Baharom and Mat Som Marwi - Hawizah, Siti Hawa; Baharom, Bahardin; Marwi, Mat Som (1995)
The track is the infrastructure of the railway system. The development of concrete sleeper becomes very important due to increase in train speed and development of long welded rails. Due to this, it is necessary to increase the weight and the strength of the concrete sleepers to resist track buckling and reduce vibration. The Light Rail Transit (LRT) and Double Tracking Systems for Keretapi Tanah Melayu Berhad (KTMB) taking full turn in easing traffic congestion is a challenge. These systems imparts modern high speed trains producing considerable amount of impact energy to the track and high frequency vibrations in the rails. Concrete sleepers, presently being widely used should absorb these forces that lead to high tensile stresses which develop cracking in these sleepers. Dynamic behaviour of these sleepers is not much known in Malaysia. It is intended to study the structural behaviour with context of Malaysian system. This preliminary investigation under the positive bending moment test, experimented for structural behaviour of the Prestressed Concrete Sleeper (PCS) under static load and dynamic loads of 1 million, 3 million and 5 million cycles.